2005
DOI: 10.1007/s00441-004-1031-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanical shear-plane between core and sheath elements of peripheral nerves

Abstract: The mechanical architecture of rat sciatic nerve has been described as a central core surrounded by a sheath, although the way in which these structures contribute to the overall mechanical properties of the nerve is unknown. We have studied the retraction responses of the core and sheath following transection, together with their tensile properties and the interface between them. Nerves were harvested and maintained at their in situ tension and then either transected entirely, through the sheath only, or thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
(18 reference statements)
3
19
0
Order By: Relevance
“…The coefficient of variations of parameter α were smaller than those of parameter μ 0 , which may due to the fact that stress is more sensitive to parameter α than μ 0 . The instantaneous shear modulus of perineurium, μ 02 , was found higher than those of the other two ultrastructures, which was consistent with the results of tensile tests (Georgeu et al, 2005;Sunderland, 1978). From histological point of view, the stiff perineurium was mainly composed of dense collagen fibrils and lamellar layers (Sunderland, 1978).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The coefficient of variations of parameter α were smaller than those of parameter μ 0 , which may due to the fact that stress is more sensitive to parameter α than μ 0 . The instantaneous shear modulus of perineurium, μ 02 , was found higher than those of the other two ultrastructures, which was consistent with the results of tensile tests (Georgeu et al, 2005;Sunderland, 1978). From histological point of view, the stiff perineurium was mainly composed of dense collagen fibrils and lamellar layers (Sunderland, 1978).…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, the epineurium was found to have the smallest stiffness which may due to the fact that it is composed of loose connective tissues and some aligned collagen fibrils (Sunderland, 1978). It has been found that the perineurium of rat sciatic nerve can bear higher tensile force before damaged (Georgeu et al, 2005) and similar function of perineurium was found from transverse elasticity in this current study. Together, the epineurium and the perineurium may provide protection against compression load.…”
Section: Discussionsupporting
confidence: 88%
“…In simplified analyses, the perineurum or interface between the nerve sheath and the core provides a shear plane that facilitates independent movement of the core (endoneurum) and the sheath (epineurum). 58,59 We suspect that the axillary nerve sheath and interface (or shear plane) protect the core from injury that could otherwise be induced by stretch involved in the pulley system that occurs during AER.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors suggest that mechanical properties of individual layers of peripheral nerves may help determine peripheral nerves' excursion and strain responses to stretch about a joint. 58,59 Excursion describes gliding of the axillary nerve relative to its nerve bed; strain is the change in axillary nerve length induced by longitudinal tensile stress. 58 Dynamic elongation of the nerve under tensile force is counteracted by transverse contraction of the nerve, which is reversible as the tensile force is relieved.…”
Section: Discussionmentioning
confidence: 99%
“…Retraction of the axotomized nerve ends usually precludes direct approximation within a few days or weeks of the trauma, requiring the use of nerve grafts to repair the defect. [3][4][5] The standard approach to repair a peripheral nerve when a gap is present is to bridge the severed ends with a segment of autologous donor nerve. When the caliber of the donor autograft matches that of the recipient nerve, in both total diameter and average axon density, superior results are obtained.…”
mentioning
confidence: 99%